I Like, I Attach, I Spend: Psychological Mechanisms Behind In Game Currency Purchases - Haga Askardo Meliala (Journal Research of Social Science, Economics, and Management, 2026)
The global video game market has seen rapid growth, particularly in Asia, where Gen Z and Millennial players increasingly engage in microtransactions within free-to-play games. Among monetization mechanisms, gacha systems have gained prominence, combining chance-based rewards with in-game item purchases. While structural mechanics partly explain spending, psychological factors such as self-congruence, parasocial interaction, character liking, character attachment, and game commitment play critical roles in driving purchase behavior. This study investigates how these relational and affective mechanisms influence in-game currency purchases in the context of Zenless Zone Zero among Indonesian players. Using a convenience sample of 207 active players, data were collected via online questionnaires and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that other-congruence positively affects character liking, which in turn enhances character attachment and purchase intention, whereas self-congruence fosters parasocial interaction and game commitment, but the indirect path to purchase intention was not statistically significant. Character attachment emerged as the strongest predictor of purchase intention, highlighting the primacy of emotionally meaningful bonds over general game commitment. These findings underscore the importance of relational and affective processes in digital game monetization and provide insights for developers seeking to optimize engagement and spending behavior.